Identification of Some New Tetrazole and Thiazolidine Derivatives Synthesized From 4-Chlorobenzoic Acid and Evaluation Their Antibacterial Effect - Maysoon Tariq Tawfiq (Journal of Global Pharma Technology, 2016)
The research includes the synthesis of some new derivatives of tetrazole and thiazolidine rings from the reactions of 2- (4-chlorophenyl)-5-hydrazinyl- 1,3,4-oxadiazole [4] with various substituted aromatic aldehydes in absolute ethyl alcohol as a solvent and presence of glacial acetic acid as a catalyst to form Schiff's bases [5-10]. The prepared new Schiff's bases [5 -10] reacted with sodium azide , and mercaptoacetic acid in THF to yield five membered rings (tetrazole ring) [11-15], and (thiazolidine ring) [16-20] in good products. The spectral methods of the prepared compounds were characterized by FT.IR, and 1HNMR for compounds [9,13,14,and 19] , besides melting points were recorded , and the purity was checked through T.L.C. technique. Antibacterial activities for some of the synthesized compounds were examined.Keywords: Heterocyclic compounds, 4-Chlorobenzoic acid, Acid hydrazide, Oxadiazole, Schiff’s bases, Tetrazole, Thiazolidine, Biological activity.